Pemberdayaan Pendidikan di Laensasi, Filipina: Integrasi Wawasan Kebangsaan, Keterampilan Mengajar dan Aksi Kemanusiaan - Ramlianto, Ramlianto; Alrasyid, Harun (Lembaga Yasin AlSys, 2025)
The International Community Service Program (KKN) held in Laensasi, Philippines, aims to empower people of Indonesian descent (Registered Indonesian Nationals, RIN) through an educational and practical approach. This program is designed to answer the challenges of the welfare of the RIN community, such as the low quality of life due to limited access to jobs and unequal community empowerment. Various activities, including skills training, introduction to Indonesian culture and geography, as well as humanitarian actions such as the construction of mosques, have been carried out to raise awareness of nationalism and the quality of life of the local community. This methodology uses the Participatory Action Research (PAR) approach. Data sources come from observation, socialization, education, as well as demonstrations and hands-on practice. The results of the study found that the main problem faced by Indonesian citizens (RINs) in the Philippines is related to welfare, which affects their level of living. This welfare problem includes an inadequate quality of life, both in terms of housing and facilities that support daily activities. This is due to limited access to jobs and a lack of equitable distribution of community empowerment, which has an impact on the low skills of the local population. In addition, the importance of raising awareness among Indonesian people there about their desire to return to their homeland is also one of the main objectives of the implementation of this international KKN program. The impact of the activity showed a positive impact in the form of increasing skills, strengthening national identity, and more optimal local economic potential. It is hoped that the implementation of this program can be a model of sustainable community empowerment that focuses on independent and inclusive development.